Chromosomal analyses of human giant diploid oocytes by next‐generation sequencing. (18th March 2021) - Kawano, Hiroomi; Yamashita, Naoki; Ito, Junya; Kashiwazaki, Naomi
Abstract: Purpose: Although giant oocytes (GOs) having about twice cytoplasmic volume compared with general oocytes in mammals including the human are rarely recovered, it is thought that GOs have potentially chromosomal abnormalities. The aim of the present study was to assess chromosome numbers in chromosome‐spindle complexes (CSCs) and polar bodies of human GOs by using micromanipulation for sampling and next‐generation sequencing (NGS) for analyses of the chromosome numbers. Methods: When recovered oocytes whose cytoplasm has lager than 140 µm or above, the oocytes were defined as GOs, and recovered GOs were vitrified. After warming, the CSCs, polar bodies, and enucleated cytoplasm were collected by micromanipulation from 3 GOs. The collected samples were analyzed by NGS. Results: Chromosomal aneuploidy in the GOs was confirmed in all the three GOs. Comparing the CSCs with the chromosomes from polar bodies, the deletion and overlapping chromosome numbers were complementary in each GO. Conclusions: The authors could collect the CSCs and the polar bodies from human GOs by micromanipulation, and then could analyze the chromosome numbers of the GOs by NGS method. As our data suggest that human GOs have chromosomal abnormalities, GOs should be excluded from clinical purpose as gamete sources for embryo transfer in the human.